Stereotyp w przestrzeni symbolicznej - Hendrykowski , Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The subject of the article is stereotypes considered in the context of symbolic space. This redefinition and reconsideration of the complex issue of stereotypes and stereotyping of diferent kinds in art and everyday life aims at demonstrating the operational usefulness of this concept in contemporary humanistic re-ection, including the sphere of art, everyday life and various fields of scientific research.